2008
DOI: 10.2353/jmoldx.2008.070153
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Validation of Total RNA Extraction Methods for MicroRNA Expression Analyses in Formalin-Fixed, Paraffin-Embedded Tissues

Abstract: Histopathology archives of well-annotated formalin-fixed, paraffin-embedded (FFPE) tissue specimens are valuable resources for retrospective studies of human diseases. Since recovery of quality intact mRNA compatible with molecular techniques is often difficult due to degradation, we evaluated microRNA (miRNA), a novel class of small RNA molecules with growing therapeutic and diagnostic potential, as an alternative analyte for gene expression studies of FFPE samples. Analyzing total RNA yield, miRNA recovery, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
155
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(167 citation statements)
references
References 29 publications
(20 reference statements)
6
155
0
5
Order By: Relevance
“…Also, it previously was shown that both the RNeasy and RecoverAll kits allow extraction of total RNA of similar integrity and suitable for microarray hybridization. 9,39 Similar findings in both of our cohorts additionally suggest that extraction protocols did not have much influence on the RNA used for library preparation. From this perspective our analysis provided additional independent validation.…”
Section: Discussionsupporting
confidence: 69%
“…Also, it previously was shown that both the RNeasy and RecoverAll kits allow extraction of total RNA of similar integrity and suitable for microarray hybridization. 9,39 Similar findings in both of our cohorts additionally suggest that extraction protocols did not have much influence on the RNA used for library preparation. From this perspective our analysis provided additional independent validation.…”
Section: Discussionsupporting
confidence: 69%
“…fragmentation, and formation of cross-links between RNA and proteins. Owing to their small size, miRNAs are less prone to degradation, 15,23 therefore, formalin-fixed paraffin-embedded samples are more suitable for miRNA than for mRNA expression analyses. Storage up to 7 years did not cause significant deterioration of miRNA quality, but older samples may exhibit loss of small RNA quality due to oxidation and fixation in nonbuffered formalin.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we identified and validated a superior-performing RNA extraction method allowing isolation of large amounts of quality RNA to perform robust miRNA expression analyses by qRT-PCR in FFPE tissues. 19 Here, we used this method to evaluate miRNA expression profiling in 31 different FFPE tissue blocks up to 11 years old. Using nine different mouse and human tissue types, we demonstrate that the original miRNA composition of frozen tissue is essentially preserved after routine fixation in formalin and long-term storage.…”
Section: Discussionmentioning
confidence: 99%
“…18 The microarray expression levels of selected miRNA species in liver NAT and spleen tissue blocks were confirmed via qRT-PCR using 10 ng of total RNA input and TaqMan microRNA assays (Applied Biosystems, Foster City, CA) as described. 19 …”
Section: Mirna Expression Profilingmentioning
confidence: 99%